AN ANALYSIS OF READING LITERACY FOR COLLEGE STUDENTS THROUGH WEBTOON AS INTERACTIVE LEARNING - Dewinur Oktavia Indah; Hanafi Wibowo (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
This research is about An Analysis of Reading Literacy for College Students through Webtoon as Interactive Learning. Webtoon is one of a way aimed to interest students in reading literacy. The purpose of this research is to know whether the use of webtoon can be interactive learning and increase reading literacy. Also, this research was conducted by using qualitative data with descriptive analysis approach and triangulation data. The subject of this research was the 3rd semester of As-Syafi’iyah Islamic University 2020/2021 academic year which consisted of 20 students and take 5 students randomly. The data were gathered through observations and interviews of the instrument. The technique of data analysis in this study is thematic analysis through the answer of interview questions then the transcript to gain the topic to become a theme. The theme used to be analyzed as a result of this study. Based on the data, the result of this research showed that webtoon can be interactive learning and increase the reading literacy of students. Learning using the webtoon more simple and easy access. In other words, webtoon can be more interested in increase reading literacy for students.